Antioxidant activity and characterization of whey protein-based beverages: Effect of shelf life and gastrointestinal transit on bioactivity. (October 2019) - Arranz, E.; Corrochano, A.R.; Shanahan, C.; Villalva, M.; Jaime, L.; Santoyo, S.; Callanan, M.J.; Murphy, E.; Giblin, L.
Abstract: Whey proteins can exhibit antioxidant activity. The objectives of this study were to formulate model whey based beverages with well-established antioxidants (plant polyphenols, vitamins and astaxanthin) to investigate (1) the antioxidant shelf life over a 24-week period and (2) the antioxidant activity after upper gastrointestinal transit. Pilot scale processing (pasteurization, ultra-high temperature or spray drying) was used to prepare beverages which were representative of current product formats. In vitro gastrointestinal digestion of test samples was performed using the standardised INFOGEST method and antioxidant activity of samples was determined using ABTS, FRAP and ORAC. Results from the antioxidant shelf life study provided evidence that powder products functionality was preserved. Whey beverages (pasteurised or spray dried) increased or maintained antioxidant activity during gastrointestinal transit. Combination of whey with additional antioxidant ingredients increased the bioactivity of formulated products; however, this greater bioactivity was altered after gastrointestinal transit, depending on processing type and antioxidant methodology. Industrial relevance: Whey protein-based antioxidant beverages could benefit the elderly consumer to meet their increased protein requirements and boost their antioxidant status. Consumer's acceptance for whey protein-based beverages often improves with clear formulations. This work generated whey protein-based UHT beverages with greater stability and clarity than pasteurised formulations. A novel combination of plant and marine antioxidants increased antioxidant activity of whey protein-based formulations. Furthermore, to suit export markets this work generated spray dried whey protein formulations that did not alter antioxidant potential. Highlights: Marjoram polyphenols and astaxanthin were combined with whey proteins. UHT processing produced clear and stable whey protein beverages. Thermal processing and simulated digestion altered bioactivity of beverages. Shelf life antioxidant activity of powder beverages was maintained during storage. Spray drying did not alter the antioxidant potential of beverages.